If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7u + 49 = -5u + 25 Reorder the terms: 49 + 7u = -5u + 25 Reorder the terms: 49 + 7u = 25 + -5u Solving 49 + 7u = 25 + -5u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '5u' to each side of the equation. 49 + 7u + 5u = 25 + -5u + 5u Combine like terms: 7u + 5u = 12u 49 + 12u = 25 + -5u + 5u Combine like terms: -5u + 5u = 0 49 + 12u = 25 + 0 49 + 12u = 25 Add '-49' to each side of the equation. 49 + -49 + 12u = 25 + -49 Combine like terms: 49 + -49 = 0 0 + 12u = 25 + -49 12u = 25 + -49 Combine like terms: 25 + -49 = -24 12u = -24 Divide each side by '12'. u = -2 Simplifying u = -2
| X^2y-3xy^2-6x^2y= | | x+2/5+x=2/3 | | 8x-4+3x=8x+14 | | a^2+2a-1=0 | | 11=-13y+3y | | -3y+4+6y= | | 6m+x=24 | | 2m-3=6m-4 | | 8(n-1)=-32 | | X-15=36 | | 2(x+8)=34 | | 3m-3=6m-4 | | 3(4x+4)+7(x-1)= | | -6y+29=3y-7 | | 12-5t=3t-20 | | -16x^2-9=0 | | 2x+48=10x-30 | | 6(m-2)+5=3m-(7+5m) | | (1-a)(1-a)(-a)=0 | | 9x^2-6x-1=0 | | (x+4)(3x+12)= | | (5/3)+4= | | 42x^4+35x^2=28 | | -16x^2-9= | | x^2-4x-2= | | 7n-24=4n+6 | | -.5c^2+1.50c+250= | | P(c)=-.5c^2+1.50c+250 | | x^2+y^2-10x+6y-4=0 | | X^3-5x^2-25x+125=0 | | 3(12.5)-50=7(12.5) | | (3(12.5)-50)=7(12.5) |